Pentingnya Manajemen Perkantoran dan Informasi dalam Sebuah Organisasi - Najihah, Wilda ‘Ainun (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2023)
Any organization, including companies, a leader is required to be able to develop a company and in developing the company a leader can apply effective leadership management by applying leadership that puts family and togetherness at the forefront, with such leadership employees will feel comfortable doing their jobs, the company will increase and be more developed if employees feel happy in doing the work given by the company. This study contains the following problem formulations: (1) What is the purpose of office administration? (2) What are the Scope of Office Management? (3) What is Management Information System? (4) What is the Importance of Management Information Systems in Organizations. Thus the purpose of the problem of this research is (1) Want to Know What is the Purpose of Office Administration? (2) Do you want to know what is the Scope of Office Management? (3) Want to Know What is a Management Information System? (4) Want to Know What is the Importance of Management Information Systems in Organizations. This study uses a qualitative method, namely the author analyzes data based on information obtained from literacy in books, journals and other scientific works. From the results obtained. The purpose of office administration in general; Implementing and developing communication skills, Implementing and developing information technology capabilities, implementing and developing the ability to plan, implement, organize and evaluate tasks that are their responsibility, implement and develop skills in managing letters/documents according to standard operations and procedures to support the main tasks of the institution, implementing and developing services for relationships so that each party benefits, implementing and developing the ability to manage financial administration